Lactobacillus in Food Animal Production—A Forerunner for Clean Label Prospects in Animal-Derived Products - Dewi, Grace; Kollanoor Johny, Anup (Frontiers in Sustainable Food Systems, 2022)
Lactobacillus, the largest genus within the lactic acid bacteria group, has served diverse roles in improving the quality of foods for centuries. The heterogeneity within this genus has resulted in the industry's continued use of their well-known functions and exploration of novel applications. Moreover, the perceived health benefits in many applications have also made them fond favorites of consumers and researchers alike. Their familiarity lends to their utility in the growing “clean label” movement, of which consumers prefer fewer additions to the food label and opt for recognizable and naturally-derived substances. Our review primarily focuses on the historical use of lactobacilli for their antimicrobial functionality in improving preharvest safety, a critical step to validate their role as biocontrol agents and antibiotic alternatives in food animal production. We also explore their potential as candidates catering to the consumer-driven demand for more authentic, transparent, and socially responsible labeling of animal products.